Solid-pseudopapillary tumor of the pancreas (Frantz's tumor), a rare entity, regarding a case - Raygoza, Jazabel; Gracia, Jorge A. (International Journal of Research in Medical Sciences, 2024)
Frantz tumor is a rare solid pseudopapillary neoplasm of the pancreas. Represents 1-2% of all the exocrine neoplasm of the pancreas. Was described for the first time in 1959. Occurs insidiously in female, young patients. The diagnosis is made casually through images, it should be suspected in a tomography as the first differential diagnosis in the presence of a large tumor, located in the head and/or tail of the pancreas with defined contours with solid and cystic portions, and rare presence of metastasis. The treatment is surgical resection of the tumor with a very good prognosis, with a high survival rate and low recurrence. A case is reported of a 31-year-old female patient, with no significant history, presenting with abdominal pain of three months duration and subsequent early satiety, without other symptoms. Clinically with the presence of a palpable tumor in the right hypochondrium, without signs of peritoneal irritation, laboratory without alterations, imaging studies with presence of tumor in the head of the pancreas. A pancreaticoduodenectomy is done, with findings and definitive histopathological report of solid pseudopapillary neoplasia delimited to the pancreas, with good postoperative evolution. Frantz tumor is a rare entity in which the majority of solid papillary neoplasms behave in a benign manner, with complete surgical resection being the mainstay of curative treatment, which leads to better results that increase survival and reduces local and distant recurrence.